Reinstatement of Spirostreptus kandyanus Humbert, 1865 and deletion of Thyropygus allevatus (Karsch, 1881) and Sphaeropoeus hercules (Brandt, 1833) in the checklist of Sri Lankan Diplopoda - Zoysa, H. K. S. De; Ukuwela, Kanishka D. B.; Wickramasinghe, S.; Nguyen, Anh D.; Hollier, John (Zootaxa, 2017)
The Diplopoda have been studied for some 250 years, but until the later part of the nineteenth century most descriptions were rather cursory and neither the species concept nor type concept were well established (Hoffman 2009). Even for well-explored regions like Europe, the description of the Diplopoda saw a proliferation of synonyms (Enghoff 1976) while the complexity of Diplopoda systematics was severely underestimated until very recently (Brewer et al. 2012).